New developments in the use of gene therapy to treat Duchenne muscular dystrophy. (February 2014) - Jarmin, Susan; Kymalainen, Hanna; Popplewell, Linda; Dickson, George
<x xml:space="preserve">Abstract</x> Introduction: Duchenne muscular dystrophy (DMD) is a lethal X-linked inherited disorder characterised by progressive muscle weakness, wasting and degeneration. Although the gene affected in DMD was identified over 25 years ago, there is still no effective treatment. Areas covered: Here we review some of the genetic-based strategies aimed at amelioration of the DMD phenotype. A number of Phase II/III clinical trials of antisense oligonucleotide-induced exon skipping for restoration of the open reading frame (ORF) of the DMD gene have recently been completed. The potential strategies for overcoming the hurdles that appear to prevent exon skipping becoming an effective treatment for DMD currently are discussed. Expert opinion: The applicability of exon skipping as a therapy to DMD is restricted and the development of alternative strategies that are more encompassing is needed. The rapid pre-clinical advances that are being made in the field of adeno-associated virus (AAV)-based delivery of micro-dystrophin would address this. The obstacles to be faced with gene replacement strategies would include the need for high viral titres, efficient muscle targeting and avoidance of immune response to vector and transgene. The new emerging field of gene editing could potentially provide permanent correction of the DMD gene and the feasibility of such an approach to DMD is discussed.